Shift selection influence in partial cycle spinning denoising of biomedical signals. (April 2016) - Rodriguez-Hernandez, Miguel A.
Highlights: Partial Cycle Spinning (PCS) denoising method for ultrasonic signals is studied. Different rules for shift selection in PCS are proposed, compared and evaluated. Quality of denoised signals using PCS varies for different selected shifts. Quality of denoised traces using PCS can be better than using Cycle Spinning. Selection of the best shifts for PCS denoising is an open problem. Abstract: Denoising of biomedical signals using wavelet transform is a widely used technique. The use of undecimated wavelet transform (UWT) assures better denoising results but implies a higher complexity than discrete wavelet transform (DWT). Some implementation schemes have been proposed to perform UWT, one of them is Cycle Spinning (CS). CS is performed using the DWT of several circular shifted versions of the signal to analyse. The reduction of the number of shifted versions of the biomedical signal during denoising process used is addressed in the present work. This paper is about a variant of CS with a reduced number of shifts, called Partial Cycle Spinning (PCS), applied to ultrasonic trace denoising. The influence of the choice of PCS shifts in the denoised registers quality is studied. Several shifts selection rules are proposed, compared and evaluated. Denoising results over a set of ultrasonic registers are provided for PCS with different shift selection rules, CS and DWT. The work shows that PCS with the appropriate choice of shifts could be the best option to denoise biomedical ultrasonic traces.